Biomechanical Responses of Neonatal Brachial Plexus to Mechanical Stretch - Singh, Anita; Shaji, Shania; Delivoria-Papadopoulos, Maria; Balasubramanian, Sriram (Journal of Brachial Plexus and Peripheral Nerve Injury, 2018)
This study investigated the biomechanical responses of neonatal piglet brachial plexus (BP) segments—root/trunk, chord, and nerve at two different rates, 0.01 mm/second (quasistatic) and 10 mm/second (dynamic)—and compared their response to another peripheral nerve (tibial). Comparisons of mechanical responses at two different rates reported a significantly higher maximum load, maximum stress, and Young's modulus (E) values when subjected to dynamic rate. Among various BP segments, maximum stress was significantly higher in the nerve segments, followed by chord and then the root/trunk segments except no differences between chord and root/trunk segments at quasistatic rate. E values exhibited similar behavior except no differences between the chord and root/trunk segments at both rates and no differences between chord and nerve segments at quasistatic rate. No differences were observed in the strain values. When compared with the tibial nerve, only mechanical properties of BP nerves were similar to the tibial nerve. Mechanical stresses and E values reported in BP root/trunk and chord segments were significantly lower than tibial nerve at both rates. When comparing the failure pattern, at quasistatic rate, necking was observed at maximum load, before a complete rupture occurred. At dynamic rate, partial rupture at maximum load, followed by a full rupture, was observed. Occurrence of the rate-dependent failure phenomenon was highest in the root/trunk segments followed by chord and nerve segments. Differences in the maximum stress, E values, and failure pattern of BP segments confirm variability in their anatomical structure and warrant future histological studies to better understand their stretch responses.
Keywords: Neonatal Brachial Plexus; injury mechanism; biomechanical properties; stretch rates